Overcoming History through Exit or Integration - Deep-Rooted Sources of Support for the European Union - Kai Gehring (Center for Economic Studies and ifo Institute (CESifo), 2020)
Preferences about the vertical distribution of power in federal systems are not well understood. I argue that negative historical experiences with higher-level governments can plausibly raise demands for exit strategies and a devolution of power. But integration, for instance delegating power from the nation-state to a supra-national level or international organization, can also serve the purpose of overcoming history by constraining nation-state actions. I specify conditions for affecting current preferences, and apply this framework to the European Union. Empirically, the quasi-random division of the French regions Alsace and Lorraine allows estimating differences in support for integration in a spatial regression discontinuity design. More negative exposure to nation-state actions causes persistently higher support for European integration in three referenda and less euroscepticism in European elections. Survey evidence supports exit and integration as two complementary alternatives, revealing preferences to move power away from the nation-state, either to the regional or European level.
Keywords: D70; F50; H70; N24; 330; nation-states; federalism; supra-national integration; international organizations; secession; minority regions; persistence; European Union support; Euroscepticism; European identity